Virgil, Aeneid 2 - Horsfall, Nicholas,Virgil (Brill, 2008)
This is Nicholas Horsfall's fourth commentary on a book of the Aeneid and in scale and approach follows closely the earlier volumes.It is aimed at the scholarly public and is not intended as a replacement for Austin's admirable school and undergraduate commentary of 1964. But so splendid an ancient text requires fresh scholarly instruments and this commentary discusses fully the acutely controversial Helen-episode (spurious), matters of linguistic and textual interpretation,, metre, prosody, grammar, lexicon and idiom, as well as Virgil's sources and the literary tradition in which he writes. Full attention is given to matters military and historiographical. New critical approaches and recent developments have been taken into account, with more attention to their spirit than to their language. A text, with translation, and three indices are included.
10.1163/ej.9789004169883.i-632
Keywords: Kommentar; Vergilius Maro; Publius; Aeneis